The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40001-022-00817-6
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab for induction of remission in patients with Crohn's disease: a systematic review and meta-analysis

Abstract: Purpose A large number of people with Crohn's disease (CD) fail to recover from conventional therapy or biological therapy. Some studies showed that adalimumab (ADA) may be an effective alternative therapy for these patients. The aim of this study was to evaluate the efficacy and safety of ADA in inducing CD remission. Methods We performed search of Pubmed/MEDLINE, Embase, CENTRAL, the Cochrane IBD Group Specialized Register, and several other data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(104 reference statements)
2
2
0
Order By: Relevance
“…our subgroup analysis demonstrated that previous exposure to IFX have less effect on the e cacy of ADA compared with patients with IFX-naïve. This is consistent with the results of Song et al [11] However, Yin et al [12] assessed the e cacy and safety of ADA in inducing and maintaining remission of participants with CD, which included four RCTs and concluded that e cacy rates were similar between the TNF-α-naïve and TNF-α exposed subgroups. We think the possibility might be that patients with previous IFX treatment probably had more severe disease for a longer period of time, which led them to receive anti-TNF therapy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…our subgroup analysis demonstrated that previous exposure to IFX have less effect on the e cacy of ADA compared with patients with IFX-naïve. This is consistent with the results of Song et al [11] However, Yin et al [12] assessed the e cacy and safety of ADA in inducing and maintaining remission of participants with CD, which included four RCTs and concluded that e cacy rates were similar between the TNF-α-naïve and TNF-α exposed subgroups. We think the possibility might be that patients with previous IFX treatment probably had more severe disease for a longer period of time, which led them to receive anti-TNF therapy.…”
Section: Discussionsupporting
confidence: 85%
“…Adalimumab(ADA), as a fully humanized TNF-α monoclonal antibody has been approved by the United States Food and Drug Administration for the treatment of moderate and severe CD in children, and recommended by the European consensus guidelines for the treatment of long-term active intestinal diseases in children [9]. Several systematic review and meta-analysis have demonstrated that ADA is safe and effective in the treatment of CD in adults [10][11][12]. However, it is unclear whether adalimumab has similar e cacy in children with CD.This systematic review aimed to examine the e cacy and safety of ADA for inducing and maintaining remission in pediatric patients with CD.…”
mentioning
confidence: 99%
“…There are five further systematic review and meta-analysis studies that evaluated the effectiveness and security of ADA in CD patients. All of these reviews reached the same conclusion as revealed by us and showed that ADA was effective and significantly improved the life quality of CD participants [34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 73%
“…Finamente, otro agente biológico significativo es el Adalimumab, debido a que ha demostrado ser más eficaz al momento de tratar la enfermedad de Crohn, poniendo a consideración que presenta un menor desarrollo de efectos secundarios, así como también una mejor respuesta frente al placebo aplicado, con tasas de remisión de entre el 16.5 al 18 (Kucharzik et al, 2020;Yin et al, 2022;Zaltman et al, 2019).…”
Section: Sinunclassified